Supportive Oncology Care at Home Intervention for Patients With Pancreatic Cancer. Issue 10 (13th October 2022) - Nipp, Ryan D.; Gaufberg, Eva; Vyas, Charu; Azoba, Chinenye; Qian, Carolyn L.; Jaggers, Jordon; Weekes, Colin D.; Allen, Jill N.; Roeland, Eric J.; Parikh, Aparna R.; Miller, Laurie; Wo, Jennifer Y.; et al.
Abstract : PURPOSE: We sought to determine the feasibility of delivering a Supportive Oncology Care at Home intervention among patients with pancreatic cancer. METHODS: We prospectively enrolled patients with pancreatic cancer from a parent trial of neoadjuvant fluorouracil, leucovorin, oxaliplatin, and irinotecan (FOLFIRINOX). The intervention entailed (1) remote monitoring of patient-reported symptoms, vital signs, and body weight; (2) a hospital-at-home care model; and (3) structured communication with the oncology team. We defined the intervention as feasible if ≥ 60% of patients enrolled in the study and ≥ 60% completed the daily assessments within the first 2-weeks of enrollment. We determined rates of treatment delays, urgent clinic visits, emergency department visits, and hospitalizations among those who did (n = 20) and did not (n = 24) receive Supportive Oncology Care at Home from the parent trial. RESULTS: From January 2019 to September 2020, we enrolled 80.8% (21/26) of potentially eligible patients. One patient became ineligible following consent because of moving out of state, resulting in 20 participants (median age = 67 years). In the first 2 weeks of enrollment, 65.0% of participants completed all daily assessments. Overall, patients reported 96.1% of daily symptoms, 96.1% of daily vital signs, and 92.5% of weekly body weights. Patients receiving the intervention had lower rates of treatment delays (55.0% v 75.0%), urgent clinic visits (10.0% v 25.0%), and emergency department visits/hospitalizations (45.0% v 62.5%) compared with those not receiving the intervention from the same parent trial. CONCLUSION: Findings demonstrate the feasibility and acceptability of a Supportive Oncology Care at Home intervention. Future work will investigate the efficacy of this intervention for decreasing health care use and improving patient outcomes.